A discricionariedade judicial na fixação da pena e a observância (do princípio) da proporcionalidade como forma de tutela do direito fundamental à liberdade - Ferreira, Ryldson Martins (2013)
This enquiry makes an analysis of the entitlement to the fundamental right to freedom in the moment of criminal sentencing. Through a concise scrutiny of the practicalities of fundamental rights and their likelihood to be restrained and circumscribed, it is investigated how the proportionality principle, which is considered a limit to limits, should interfere to ensure effective protection of fundamental rights, particularly the fundamental right to freedom. Therefore, the many polemical aspects of proportionality, as well as the other punitive interrelated principles are addressed. It is also endeavored a dissection of the individualized sentencing process and its foremost role in the Democratic State of Law. In order to do so, it is established a set of guidelines on how the judge must proceed, either to evaluate the precise circumstances relevant to the given existent situation or to measure their significance. Thus, some of the interconnected criteria found in doctrine are displayed. As a final point, it is stated that Judges must be led by the proportionality principle when conducting the sentencing process, with the objective of preventing arbitrary and capricious punishment, and consequently, violations to the fundamental right to freedom.